Amplifying time-harmonic thermal signal in spinning lock-in thermography - Yanxiang Wang; Dong Wang; Xiaochang Xing; Pei-Chao Cao; Qiang-Kai-Lai Huang; Hao-Ran Yan; Hongsheng Chen; Ying Li (Communications Physics)
Abstract Time-harmonic thermal signals (or thermal waves) are widely used in non-destructive testing (NDT), particularly in lock-in thermography (LIT), an infrared-based technique for material evaluation. LIT relies on modulated thermal signals to probe material properties and detect structural defects with high sensitivity. However, traditional LIT methods are often limited to static heat sources or samples, restricting their use in dynamic scenarios. Moreover, very few studies have focused on the characteristics of thermal waves during their propagation, which is crucial for the understanding of dynamic heat transfer. This work presents a dynamic model for LIT that emphasizes the propagation characteristics of time-harmonic thermal signals. Through theoretical analysis, simulation modeling, and experimental measurements, we investigate the propagation behaviors of these thermal signals in double-layer and triple-layer models under various conditions. Our findings reveal the amplitude amplification effect of thermal signals in time-harmonic heat transfer, enabling thermal analysis in moving materials or mechanical structures, and show the potential application in NDT. This may lay a foundation for the development of advanced thermal-wave based diagnostic methods and the exploration of novel heat transfer mechanisms in dynamic systems.